Pengaruh Kualitas Produk dan Iklan Terhadap Minat Beli Ulang Shampo Rejoice - Lavenia Putri Mareta; Tri Kurniawati (Jurnal Ecogen, 2020)
This study aims to determine the effect of product quality and advertising on the repurchase interest of shampoo rejoice. This type of research is descriptive research. The study population was students of Padang State University who had used Sampo Rejoice with a purposive sampling technique. Data collection techniques used were questionnaires and documentation studies. The data analysis technique used is descriptive analysis and inductive analysis using multiple linear regression analysis. The results showed that: (1) There was a significant influence of product quality on repurchase intention, seen from sig 0,000 <0.05, (2) There was a significant effect of advertising on repurchase intention, seen from sig 0.018 <0.05, (3 ) there is a significant influence on product quality and advertising on repurchase intention, as seen from sig 0,000 <0.05. The contribution of product quality and advertising to repurchase interest amounted to 37.7%, while the remaining 62.3% was contributed by other factors not examined in this study.Keywords: product quality, advertising, repurchase interests